Faculty bargaining : change and conflict - Garbarino, Joseph W.; Aussieker, Bill (New York : McGraw Hill Education, 1975)
Among the truly new-but probably permanent--factors in American academic life are organizations patterned on the models of industrial unions to represent teachers and scholars in negotiations with colleges and universities on matters of compensation and working conditions. It is not yet clear that the new patterns will be all pervasive. The best guess is that they will not, but that there will always be fertile soil for them, at least on campuses where faculty participation in institutional governance is minimal.
1. The Challenge of institutional change -- 2. Patterns of faculty representation in governance -- 3. Faculty unions: patters of organization -- 4. Collective bargaining: the parties and their relationships -- 5. Collective bargaining: evaluating the issues -- 6. Community colleges without community -- 7. Academic unionism in great Britain -- 8. A Recapitulation.
Includes bibliographical references and index.
Keywords: COLLECTIVE BARGAINING